Design, sizing and economic feasibility of a hybrid PV/diesel/battery based water pumping system for farmland. Issue 6 (3rd May 2022) - Abid, Muhammad Zeeshan; Yousif, Muhammad; Ullah, Saleem; Hassan, Muhammad
ABSTRACT: Renewable energy systems are the promising source of future sustainable energy. Presently, energy systems based on hybrid renewables sources are lucrative and have a negligible carbon footprint. These types of systems are evolving as a progressively successful choice for the rural areas especially the accessibility of energy from the grid is poor. This study exhibits optimum design, sizing, and economic feasibility of PV- and diesel-based renewable energy systems. Particular environmental conditions, specifications of the system, and daily energy requirement data of the specific site in the San Joaquin Valley, CA, USA are carried out in order to validate the water required for the reference crop. The crop has different development stages, and it requires a different amount of water for each stage. In addition to water demand, which is our irrigation load, farmland residential energy requirements were also considered. Six distinctive ideal setups, viz. PV/battery, PV/diesel and battery, wind/battery, PV/wind/Diesel generator & battery, wind/PV/battery and Diesel generator were thoroughly examined in respect of net present cost (NPC) and cost of energy (COE) to decide most financially appropriate choice. For financial investigation and viable sizing, all the essential simulations are done utilizing the HOMER software (Hybrid Optimization Model for Electric Renewable) programming. Results obtained from simulations depict that PV/diesel/battery is the optimum arrangement for the particular site. The purpose of this work lies in utilizing the tools from HOMER and successively to do technical as well as economical investigation in addition to environmental aspects of a proposed Hybrid Renewable Energy System.